A new age of uncertainty? Implications for monetary policy - Jens Weidmann (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2022)
Central banks have faced a succession of crises over the past years as well as a number of structural factors such as a transition to a greener economy, demographic developments, digitalisation and possibly increased onshoring. These suggest that the future inflation environment will be different from the one we know. Thus uncertainty about important macroeconomic variables and, in particular, inflation dynamics will likely remain high. Discussion on what this could mean for monetary policy
Keywords: 330